Schedule contingency analysis for transit projects using a simulation approach - Gurgun, Asli Pelin; Zhang, Ye; Touran, Ali (Journal of Civil Engineering and Management, 2013)
This paper presents a probabilistic method to establish schedule contingency levels based on percent completion of the project. The objective is providing a distribution for contingency for various percent completion levels which allows the project owner/manager to choose the schedule contingency at their comfort level. The proposed method is applied on real data from a number of US transit projects and actual schedule overruns for different phases of the project development (preliminary engineering, final design and construction) are analyzed. These values are used to establish the required contingency at the conclusion of each of the mentioned project phases. Additionally, using these values, the required contingency at various points during the construction phase (such as 25% and 50% completion) is calculated and reported. This approach can be used by project owners to plan realistic schedules during various phases of the project, providing better control on duration and the opportunity for being prepared to take necessary action in case the available schedule contingency falls below reasonable levels.